Hospital Stay Considerations in Hypermobile Ehlers-Danlos Syndrome: An Exemplary Case With Insights for Coexisting Symptoms - Jamie E. Clarke; Julio Santana; Efren C. Manjarrez (Annals of Internal Medicine: Clinical Cases)
Ehlers-Danlos syndrome, hypermobility type, is a complex medical condition understood to be a genetic disorder resulting in abnormal collagen synthesis. It is characterized by joint hypermobility as well as skin laxity, poor wound healing, and other manifestations. It may present in conjunction with autonomic, neurologic, and immune abnormalities. Hypermobility spectrum disorder is similarly characterized by joint hypermobility but holds less extensive diagnostic criteria. When in the hospital setting, systemic differences resulting from hypermobility syndromes must be recognized to avoid harm. Here, we present the first case, to our knowledge, of a full hospital course with hypermobility syndrome–comorbidity-related complications described.